Obesity and Environmental Risk Factors Significantly Modify the Association between Ischemic Stroke and the Hero Chaperone C19orf53 - Irina Shilenok; Ksenia Kobzeva; Alexey Deykin; Vladimir Pokrovsky; Evgeny Patrakhanov; Olga Bushueva (Life)
The unique chaperone-like properties of C19orf53, discovered in 2020 as a “hero” protein, make it an intriguing subject for research in relation to ischemic stroke (IS). Our pilot study aimed to investigate whether C19orf53 SNPs are associated with IS. DNA samples from 2138 Russian subjects (947 IS and 1308 controls) were genotyped for 7 C19orf53 SNPs using probe-based PCR. Dominant (D), recessive (R), and log-additive (A) regression models in relation to the effect alleles (EA) were used to interpret associations. An increased risk of IS was associated with rs10104 (EA G; Pbonf(R) = 0.0009; Pbonf(A) = 0.0004), rs11666524 (EA A; Pbonf(R) = 0.003; Pbonf(A) = 0.02), rs346158 (EA C; Pbonf(R) = 0.006; Pbonf(A) = 0.045), and rs2277947 (EA A; Pbonf(R) = 0.002; Pbonf(A) = 0.01) in patients with obesity; with rs11666524 (EA A; Pbonf(R) = 0.02), rs346157 (EA G; Pbonf(R) = 0.036), rs346158 (EA C; Pbonf(R) = 0.005), and rs2277947 (EA A; Pbonf(R) = 0.02) in patients with low fruit and vegetable intake; and with rs10104 (EA G; Pbonf(R) = 0.03) and rs11666524 (EA A; Pbonf(R) = 0.048) in patients with low physical activity. In conclusion, our pilot study provides comprehensive genetic and bioinformatic evidence of the involvement of C19orf53 in IS risk.